Dentists in Nepal: A Situation Analysis - Shrestha, Rabindra Man; Shrestha, Sujita; Kunwar, Nischal (Journal of Nepal Health Research Council, 2017)
Background: Human resource data is essential for planning and implementation of health care delivery system. However, very few information is available on dental health human resource in the country. The aim of study was to assess the number of dentists in the country and to explore their distribution according to demographic and professional characteristics.Methods: A census was performed during July 2015 to July 2016 about the Nepali dentists. The study assessed demographic and professional characteristics of dentists including age, gender, ethnicity, education attainment, university, country/year of graduation, and work place using data collection sheet by trained data collectors. For those not accessible for direct contact, the information was obtained through secondary data. Data entry was done in CSPro software application and was analyzed in SPSS 20. Results: The total number of registered Nepali dentists was 1803 with 419 specialists until June 2015. The male to female ratio was 1:1.46. Among all; 1318 (73%) were present in the country, 1047 (58%) were professionally active, and 1366 (76%) were below the age of 35 years. Among the professionals; 831 (79%) were employed in private sector and 601 (57%) worked in Kathmandu valley.Conclusions: The dentist-population ratio is decreasing exponentially in capital and major cities of Nepal however it remains very high in rural areas. Compared to other provinces,Province 6 and Province 7 lack service of dentists.